Assessment of Regional Myocardial Work in Rats. (February 2015) - Espe, Emil K.S.; Aronsen, Jan Magnus; Eriksen, Guro S.; Zhang, Lili; Smiseth, Otto A.; Edvardsen, Thor; Sjaastad, Ivar; Eriksen, Morten
Abstract : Background—: Left ventricular (LV) motion and deformation is dependent on mechanical load and do therefore not reflect myocardial energy consumption directly. Regional myocardial work, however, constitutes a more complete assessment of myocardial function. Methods and Results—: Strain was measured using high-resolution phase-contrast MRI in 9 adult male rats with myocardial infarction (MI) and in 5 sham-operated control animals. Timing of LV valvular events and LV dimensions were evaluated by cine MRI. A separate cohort of 14 animals (MI/sham=9/5) underwent measurement of LV pressure concurrent with identification of valvular events by Doppler-echocardiography for the purpose of generating a standard LV pressure curve, normalized to valvular events. The infarctions were localized to the anterolateral LV wall. Combining strain with timing of valvular events and a measurement of peak arterial pressure, regional myocardial work could be calculated by applying the standard LV pressure curves. Cardiac output and stroke work was preserved in the MI hearts, suggesting a compensatory redistribution of myocardial work from the infarcted region to the viable tissue. In the septum, regional work was indeed increased in MI rats compared with sham (median work per unit long-axis length in a mid-ventricular slice: 241.2 [224.1–271.2] versus 137.2 [127.0–143.8] mJ/m; P <0.001). Myocardial work in infarcted regions was zero. Additionally, eccentric work was increased in the MI hearts. Conclusions—: Phase-contrast MRI, in combination with measurement of peak arterial pressure and MRI-derived timing of valvular events, represent a noninvasive approach for estimation of regional myocardial work in rodents. Abstract : Supplemental Digital Content is available in the text.